Program Bina Keputrian dalam Mencegah Perilaku Hedonisme dan Sekularisme Siswi: Female Development Program in Preventing Hedonistic and Secularist Behavior in Female Students - Febrianty, Rizka Amelia; Komariah, Kokom Siti; Budiyanti, Nurti (STAI Publisistik Thawalib Jakarta, 2024)
Many female students dress in ways that indicate hedonism and engage in dating behaviors in the school environment that reflect secularism. This study aims to describe the activities of the female student program in preventing hedonistic and secular behaviors at Public vocational secondary schools 1 Katapang. This research uses a qualitative approach with a case study method. Data collection involved interviews, observations, and documentation. Data processing included condensation, data presentation, and drawing conclusions. Data validity was ensured through technique and source triangulation as well as confirmability. The research findings are: (1) Amaliah knowledge development: Strengthening Islamic brotherhood, Tahfidz and daily prayers programs, and Character building with noble ethics. (2) Women's development: The position of women, the obligation to cover and protect modesty, manners of speaking, and self-care. (3) Creativity development: Cooking classes, crafts, and public speaking. Conclusion: The female student program is effective in shaping better character among students, strengthening morality, enhancing practical skills, and making a significant contribution to preventing hedonism and secularism among female students.